2013
DOI: 10.1007/s12199-013-0373-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between mobile phone use and depressed mood in Japanese adolescents: a cross-sectional study

Abstract: Objectives Mobile phones are commonly used by adolescents. The aim of this study was to clarify associations between duration of mobile phone use and psychological mood in high school students. Methods This cross-sectional study included 2,785 high school students in Niigata, Japan. A self-administered questionnaire was used to elicit information on sex, school year, hours of mobile phone use, psychological mood status, and possible confounders. Psychological mood outcomes were evaluated with the Mood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 11 publications
7
50
2
Order By: Relevance
“…On the other hand, PIU and study and exercise habits were significantly related, but for some grades, the associations were not significant. Our study also found the same relationship pattern between duration of Internet usage and lifestyle habits (sleep, study, and exercise), suggesting that junior high-school students experience sleep deprivation because of their Internet use (Tables 4 and S2), which is consistent with previous reports 36 and supports our results regarding the association between PIU and lifestyle habits. Previous studies have also reported a relation between PIU and both academic performance 37 and physical activity, 33,36 although such analyses by grade have not been sufficient.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, PIU and study and exercise habits were significantly related, but for some grades, the associations were not significant. Our study also found the same relationship pattern between duration of Internet usage and lifestyle habits (sleep, study, and exercise), suggesting that junior high-school students experience sleep deprivation because of their Internet use (Tables 4 and S2), which is consistent with previous reports 36 and supports our results regarding the association between PIU and lifestyle habits. Previous studies have also reported a relation between PIU and both academic performance 37 and physical activity, 33,36 although such analyses by grade have not been sufficient.…”
Section: Discussionsupporting
confidence: 92%
“…Our results of the cross-sectional analyses, where we found an increase in self-reported health symptom reports in relation to various self-reported usage measures, are in line with other cross-sectional studies on symptoms, mental health or sleeping problems (Byun et al 2013;Ikeda et al 2014;Koivusilta et al 2007;Redmayne et al 2013;Roser et al 2016a;Schoeni et al 2015b;Soderqvist et al 2008). …”
Section: Discussionsupporting
confidence: 92%
“…In a cross-sectional Korean study, feeling of discomfort and dry skin were associated with the number of outgoing calls per day and dry skin, fatigue and dizziness were associated with average duration per call (Byun et al 2013). Ikeda et al (2014) found associations between mobile phone use and depressed mood or fatigue, respectively in 2785 Japanese high school students. In a representative Finnish sample of 7300 adolescents, high-mobile phone users showed more symptoms of depression and sleep disturbances than low-mobile phone users (Koivusilta et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Similar findings come from recent studies linking symptoms of mental ill health, depression and anxiety to problematic mobile phone use (Augner and Hacker 2012;Ha et al 2008;Yen et al 2009), to problematic internet use (Kaess et al 2014;Ko et al 2012) and to amount of mobile phone use which is expected to partly reflect problematic use (Ikeda and Nakamura 2014;Thomée et al 2011). Similar to these studies, our cross-sectional study cannot clarify the direction of these associations.…”
Section: Hrqol and Problematic Mobile Phone Usesupporting
confidence: 71%